Rodinný dům - Burešová, Kristýna; Kristýna Burešová (České vysoké učení technické v Praze, 2022)
Zadáním bakalářské práce je rodinný dům pro pětičlennou rodinu na jedné z parcel nově vznikající zástavby na území Prahy Lochkov. Řešené území se nachází v těsné blízkosti přírodní rezervace Slavičí údolí a leží na hranici s částí Prahy Radotín. Téměř čtvercová parcela svažující se od jihovýchodu k severozápadu má ve svém středu výrazný terénní zlom, který umožňuje koncipovat objekt jako dům ve svahu se vstupem do vyššího podlaží. Motiv svahu se objevuje také v interiéru; je vyjádřen schodištěm umístěným v podélné ose objektu, která směřuje ke Slavičímu údolí. Tato osa je ještě zvýrazněna světlíkem v hřebenu střechy, který na obou stranách domu přechází v prosklené pásy, které dům dělí přesně uprostřed. Objekt má jednoduchý tvar s obdélníkovým půdorysem a sedlovou střechou, je kompaktní a nečlenitý, což vychází z hlavního tématu tohoto projektu – rodina = semknutost a pospolitost.

The Bachelor thesis addresses the design of a detached house for family with five members, which is located on one of the plots within a newly built development in the district of Prague Lochkov. That area of interest is situated in the vicinity of the Slavičí údolí nature reserve lying on the border with the Radotín district of Prague. The plot is almost square-shaped sloping from the South-East to the North-West. It has a significant terrain break in the middle, which allows for the design of a house in a slope with the entrance section being on a higher floor. The downward gradient is also incorporated in the interior with the staircase following the slope gradient. The axis of the house, which is directed to Slavičí údolí, is also highlighted by a skylight in the roof and a glass strip that continues down the sides of the house. These glass elements devide the house into two parts. The house has a simplistic shape, a rectangular-shaped plan and a gable roof. It is compact and solid, which is in harmony with the theme of the project – family = unity and community.
Family House
Keywords: rodinný dům; dům ve svahu; sedlová střecha; terénní zlom; a detached house; a house in a slope; a gable roof; a terrain break